Preserving Vision and Preventing Complications: A Case Report on the Diagnosis and Management of Chronic Angle Closure Glaucoma - Desi Ayu Wulandari; Oktarina Nila Juwita (Universitas Malahayati Lampung, 2024)
ABSTRACT This case report presents the clinical presentation and management of a 68-year-old male with chronic angle closure glaucoma. Upon examination, the right eye (OD) exhibited a significant decline in visual acuity to 1/300. Findings included conjunctival congestion (CVI +) and absence of posterior conjunctival vessel congestion (PCVI -), corneal opacification and edema, shallow anterior chamber, midriasis of the pupil, and absence of direct and consensual light reflexes (−). Additionally, lens opacification and chemosis (+) were observed. Conversely, the left eye (OS) had a visual acuity of 6/30 with an intraocular pressure (IOP) of 6/15. Similar to the right eye, it displayed corneal opacification and edema, a shallow anterior chamber, midriasis of the pupil, absence of light reflexes (direct and consensual), lens opacification, and chemosis (+). This case underscores the importance of early diagnosis of chronic angle closure glaucoma to prevent adverse prognostic outcomes. Keywords: Chronic Angle Closure Glaucoma, Vision, Preventing Adverse Outcomes